Polityczna gra o prawną regulację procedury in vitro – analiza wybranych aspektów debaty w przestrzeni medialnej (Politeja, 2013)
The politics game for regulation of in vitro fertilisation procedure – the aspects of debate in the media sphere analysis The purpose of the study, it has been mentioned in this article, was to describe the course and the range of public debate on some bioethical problems. The author presented the analysis of the articles and information, it had been published in public web portals and websites, in which the writers had referred specifically to the legislative proposals of in vitro fertilisation procedure, and to the Health Minister’s announcement of in vitro financing program from the public budget. The study includes the analysis of the statements of political and religious (Catholic) community’s representatives, medical and scientific experts and journalists. As a result of the study, five dimensions, which describe the course and range of the debate in the media sphere, has been presented.